TRANSFORMATION OF BPI SERVICES IN THE DIGITAL ERA: A CASE STUDY OF PREVENTIVE AND CURATIVE MENTAL HEALTH EFFORTS AMONG GENERATION Z STUDENTS IN THE FACULTY OF DA'WAH - Muhammad Radja Muhibbullah; Ira Wirtati (Journal Analytica Islamica, 2026)
This study examines the digital transformation of Islamic Guidance and Counseling (Bimbingan Penyuluhan Islam/BPI) services in preventive and curative mental health efforts among Generation Z students at the Faculty of Da’wah and Communication, UIN Sumatera Utara. Using a qualitative case study approach, data were collected through observation, in-depth interviews, and documentation. The findings show that BPI services have shifted from conventional face-to-face counseling to cyber-counseling through platforms such as WhatsApp, Instagram, and Zoom, which are more flexible, accessible, and perceived as more private by students. Preventive efforts are implemented through digital da’wah literacy, including educational content on stress management, gratitude, patience, and Islamic self-strengthening, while curative efforts are carried out through spiritually based online counseling, such as Qur’anic motivation, prayer guidance, and digital religious reflection. The novelty of this study lies in demonstrating that the digital transformation of BPI is not merely a technical shift of communication media, but an integrative service model that combines preventive mental resilience and curative spiritual intervention within a digital environment. This study contributes to the development of an adaptive and value-based Islamic counseling framework for higher education, while also highlighting key challenges, including limited nonverbal communication, response time constraints, absence of standard operating procedures, and concerns over data confidentiality.